Multiple-locus variable-number tandem-repeat analysis (MLVA) genotyping of human Brucella isolates in Malaysia - Tay, B.Y.; Ahmad, N.; Hashim, R.; Zahidi, J.M.; Thong, Kwai Lin; Koh, X.P.; Noor, A.M. (BMC, 2015)
Background: Brucellosis is one of the most common zoonotic diseases worldwide. It can cause acute febrile illness in human and is a major health problem. Studies in human brucellosis in Malaysia is limited and so far no genotyping studies has been done on Brucella isolates. The aim of the study was to determine the genetic diversity among Brucella species isolated from human brucellosis, obtained over a 6-year period (2009-2014). Methods: In this study, the genotypic characteristics of 43 human Brucella melitensis isolates were analysed using multiple-locus variable-number tandem-repeat analysis (MLVA) which consisted of eight minisatellite loci (panel 1) and eight microsatellite loci; panels 2A (3 microsatellite loci) and panel 2B (5 microsatellite loci). Two human Brucella suis isolates were also investigated using the MLVA assay. Results: Using panel 1 (MLVA8), two genotypes namely genotype 43 and 44 were obtained from the 43 B. melitensis isolates. Using the combination of panels 1 and 2A loci (MLVA11), two genotypes were obtained while using the complete panels 1, 2A and 2B, nine genotypes were obtained. The polymorphisms in using the complete panels (MLVA16) were observed in three loci from panel 2B, which showed a diversity index higher than 0.17. All B. melitensis isolates were closely related to the East Mediterranean group. For B. suis isolates, only genotype 6 and genotype 33 were obtained using panel 1 and MLVA11 respectively. Conclusion: In conclusion, the results of the present study showed a low genetic diversity among B. melitensis and B. suis isolates from human patients. Based on the MLVA16 assay, B. melitensis belonging to the East Mediterranean group is responsible for the vast majority of Brucella infections in our Malaysian patients. To our knowledge, this is the first genotyping study of human Brucella isolates in Malaysia.